The Economics Profession and the Making of Public Policy - Nelson, Robert H. (Journal of Economic Literature, 2016)
Robert H. Nelson has been a member of the economics staff of the Office of Policy Analysis of the U.S. Department of the Interior since 1975. He thanks Christopher Leman for his particular helpfulness over many years in identifying literature on American government and for comments and criticisms from the viewpoint of a political scientist on several drafts of this article. In addition, Donald Bieniewicz, Robert Crandall, Robert Davis, Herbert Fullerton, Jon Goldstein, Joan Hartmann, Ted Heintz, Evan Kwerel, Larry Lane, Ross Marcou, John Schefter, Eugene Steuerle, Richard Stroup, Richard Wahl, and Jeffrey Wasserman-all past or presentfirst-hand observers of the policy-making process-read earlier drafts and made helpful comments.